Efektivitas Bantuan Langsung Tunai Dana Desa Bagi Masyarakat Miskin Terkena Dampak Covid-19 Di Desa Sambangan Kecamatan Sukasada Kabupaten Buleleng - Made Ngurah Duwipantara; Anantawikrama Tungga Atmadja (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to find out how the implementation of direct cash assistance was and how effective the direct cash assistance from village funds was for the poor affected by COVID-19 in Sambangan Village, Sukasada District, Buleleng Regency. Methods This research uses a qualitative approach with the type of descriptive research. The data analysis used is a qualitative descriptive method by analyzing data based on existing theories by examining and examining in depth and then analyzing it to draw conclusions. This research was conducted in Sambangan Village, Sukasada District, Buleleng Regency. The population of this study is the implementer in this case the village head and treasurer as well as the recipient community and those who do not receive the Village Fund Direct Cash Assistance in Sambangan Village, Sukasada District, Buleleng Regency. The data of this research were collected by interview method, observation method, and documentation study method. The results of this study stated that from the aspect of timeliness, the officers had carried it out on time so that the distribution of BLT funds from the I to Stage IV villages had been going well. In terms of accuracy in making choices, the village government has worked in accordance with applicable regulations. In terms of targeting accuracy, it is right on target.